Ratio : the simple codes behind the craft of everyday cooking - Ruhlman, Michael, 1963- (New York, NY : Scribner, 2009)
Cooking with ratios will unchain you from recipes and set you free. With thirty-three ratios and suggestions for enticing variations, "Ratio" is the truth ofcooking: basic preparations that teach us how the fundamental ingredients of the kitchen -- water, flour, butter and oils, milk and cream, and eggs -- work. Change the ratio and bread dough becomes pasta dough, cakes become muffins become popovers become crepes.
The ratios -- What is a ratio, and why is it important? -- The all-important scale -- Using this book -- The truth of cooking --
Keywords: Cooking; Ratio and proportion; Cooking; Ratio and proportion; Matlagning; Cookbooks; Cookbooks